Formulation and Characterization of a Sleeping Mask Gel Utilizing Watermelon (Citrullus lanatus L.) White Rind Juice - Thomas, Nurain; Paneo, Mohamad Aprianto; Suleman, Putri Rawe (Jurnal Farmasi Teknologi Sediaan dan Kosmetika, 2025)
A laboratory-based study was conducted to formulate and evaluate a sleeping-mask gel incorporating juice from the white rind of watermelon (Citrullus lanatus L.) with Hydroxypropyl Methylcellulose (HPMC) as the gelling agent. White-rind juice was prepared and incorporated into gel bases containing 2–5% HPMC with fixed excipients. Characterization encompassed organoleptic properties, homogeneity, pH, adhesion, spreadability, and viscosity according to topical gel quality criteria. Acceptable organoleptic attributes and uniformity were observed for all formulas. pH values (~4.0–6.0) lay within the facial-skin-compatible range. Increasing HPMC concentration was associated with greater adhesion, with minimum criteria satisfied from 4% HPMC. Desired spreadability was obtained at lower-to-intermediate HPMC levels, while viscosity testing indicated that 4–5% HPMC achieved application comfort alongside structural stability. Overall performance identified the 4% HPMC gel as providing the most balanced combination of spreadability, adhesion, and viscosity, yielding a clear and stable preparation. These findings support the feasibility of developing a sleeping-mask gel from watermelon white-rind juice, with a 4% HPMC base recommended as the optimal formulation.